The Effectiveness of Islamic Education Financing Management Amid Government Spending Efficiency Policies - Yusra wati; Hamdi Abdul Karim (FiTUA: JURNAL STUDI ISLAM, 2025)
This study aims to evaluate the effectiveness of Islamic education fund management at Madrasah Tsanawiyah (MTs) in Padang Panjang City in response to government spending reduction policies. The method used is a descriptive quantitative approach with random sampling techniques, involving 10 respondents from four MTs. Data collection was conducted through closed-ended questionnaires, semi-structured interviews, and documentation, which were then analyzed using descriptive statistics. The research findings indicate that the management of education funds is considered fairly effective. The planning aspect received the highest score (4.2), indicating that educational institutions are able to prepare budgets in accordance with existing priorities and needs. Financial implementation and reporting were also effective (with scores of 3.8 and 4.0, respectively), although there were some challenges such as delays in BOS funds and a lack of training for human resources. Meanwhile, stakeholder involvement was still relatively low (3.5), indicating the importance of increasing community participation in the financial decision-making process. The conclusion of this study is that the effectiveness of fund management at MTs can still be maintained despite fiscal efficiency policies, provided that the principles of transparency, accountability, and community participation are strengthened. These findings provide significant recommendations for madrasahs and the government to improve the quality of sharia-based financial management and digital technology.